A Study on Role of Clinical Pharmacist in Identification and Prevention of Medication Errors at a Teritiary Care Hospital - Gandage, Manjunath; Ninne, Sheetal; salimath, Pooja; Reddy, Prathusha; Buchanalli, Shweta; Reddy, Harshitha; Samson, Kishwanth (Indian Journal of Pharmacy Practice)
Introduction: Medication errors are at forefront and common provision of modern healthcare and one of the many hazards of hospitalization. The problem is of multidisciplinary and multifactorial in nature. Objective: Identification and prevention of medication errors. Methods: A prospective observational study was conducted over a period of 6 months in a tertiary care hospital. Patients were selected randomly by considering the study criteria. Medication errors were analyzed by using Treatment chart review. The severity levels of medication errors have been analyzed by using the National Coordinating Council for Medication Error Reporting and Prevention (NCCMERP) proposed index for categorizing medication errors. Results: A total of 681 cases were selected randomly, in which 199 (29.22%) patients showed, 221 medication errors. Out of which 128 (57.91%) errors were actual errors and 93 (42.08%) errors were categorized as potential errors. Prescribing errors were 82.80%, followed by Administration errors 23 (10.40%), Dispensing errors 08 (3.61%) and 07 (3.16%) were Monitoring errors. Anti-infective drugs were the most common class of drugs in which errors occurred 45 (21.02%). Most of the errors in our study resulted in No Error 42.53% (category A), 44.34% (category B, C and D) resulted in Error No Harm, 13.12% (category E, F, G, H) resulted in Error Harm. No incidence of Error Death was reported. Conclusion: The incidence of medication errors was significantly high and it is essential to establish medication error reporting system. Study results shows that there were more number of potential errors which can be preventable. Clinical pharmacist can play a vital role in Identification and prevention of medication errors
Keywords: Medication errors; Clinical Pharmacist; Antibiotics.